Study on solidified material from dredged sediment, fly ash, and blended Portland cement using the response surface method - Thai, Tien-Dat; Huynh, Ngoc Minh; Luu, Tuyen; Kieu Do Trung, Kien; Nguyen Vu Uyen, Nhi; Do Quang, Minh (Vietnam Journal of Science and Technology, 2024)
Treating dredged sediment is a complex processing and ongoing challenge. To utilize dredged sediment for the landfill or construction purposes, a material fabricated from a mixture of dredged sediment, Portland cement, and fly ash, was cured under room temperature and hydrothermal condition at 180 °C and 0.9 MPa pressure for 16 hours. The response surface methodology was used to evaluate the compressive strength of the material, with the range of factors investigated being the dredged sediments/solid ratio (0.3-0.9), cement/fly ash ratio (2-4), and water/solid ratio (0.45-0.55). The fitting models offered an accurate and reliable match to the actual data. The optimum mix proportions of two curing conditions were obtained using total desirability function, meet multi-objective criteria. This result finger out hydrothermal curing significantly enhances treatment capacity of dredged sediment, with a lower CO2 emission in the mixture compared to ambient curing. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR) were used to figure out the difference between the minerals formed in the material under two curing conditions, such as tobermorite.